Reference genomes of the two cultivated jute species. Issue 11 (8th July 2021) - Zhang, Lilan; Ma, Xiaokai; Zhang, Xingtan; Xu, Yi; Ibrahim, Aminu Kurawa; Yao, Jiayu; Huang, Huaxing; Chen, Shuai; Liao, Zhenyang; Zhang, Qing; Niyitanga, Sylvain; Yu, Jiaxin; et al.
Summary: Cultivated jute, which comprises the two species Corchorus capsularis and C. olitorius, is the second most important natural fibre source after cotton. Here we describe chromosome‐level assemblies of the genomes of both cultivated species. The C. capsularis and C. olitorius assemblies are each comprised of seven pseudo‐chromosomes, with the C. capsularis assembly consisting of 336 Mb with 25, 874 genes and the C. olitorius assembly containing 361 Mb with 28 479 genes. Although the two Corchorus genomes exhibit collinearity, the genome of C. olitorius contains 25 Mb of additional sequences than that of C. capsularis with 13 putative inversions, which might give a hint to the difference of phenotypic variants between the two cultivated jute species. Analysis of gene expression in isolated fibre tissues reveals candidate genes involved in fibre development. Our analysis of the population structures of 242 cultivars from C. capsularis and 57 cultivars from C. olitorius by whole‐genome resequencing resulted in post‐domestication bottlenecks occurred 2000 years ago in these species. We identified hundreds of putative significant marker‐trait associations (MTAs) controlling fibre fineness, cellulose content and lignin content of fibre by integrating data from genome‐wide association studies (GWAS) with data from analyses of selective sweeps due to natural and artificial selection in these two jute species. Among them, we further validated that CcCOBRA1 and CcC4H1 regulate fibre quality in transgenic plants via improving the biosynthesis of the secondary cell wall. Our results yielded important new resources for functional genomics research and genetic improvement in jute and allied fibre crops.